2015
DOI: 10.1016/j.pmpp.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gene expression profiles as they relate to the adult plant leaf rust resistance in the wheat cv. Toropi

Abstract: Leaf rust, caused by the foliar pathogen Puccinia triticina is a major disease of wheat in the southern region of Brazil and invariably impacts on production, being responsible for high yield losses. The Brazilian wheat cultivar Toropi has proven, durable adult plant resistance (APR) to leaf rust, which uniquely shows a pre-haustorial resistance phenotype. In this study we aimed to understand the interaction between P. triticina and the pre-haustorial APR in Toropi by quantitatively evaluating the temporal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 40 publications
(41 reference statements)
1
31
0
2
Order By: Relevance
“…Although some transcripts continued to show upregulation in subsequent time points. An increase in chitinase and glucanase gene expression has been observed upon infection with stripe and leaf rust pathogen by Casassola et al (2015) and Dobon et al (2016), respectively. Pathogenesis related transcripts with Barwin, CAPS and Bet_v_1 domain were identified only in the resistant genotype WL711+ Lr57 indicating a direct link to Lr57 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although some transcripts continued to show upregulation in subsequent time points. An increase in chitinase and glucanase gene expression has been observed upon infection with stripe and leaf rust pathogen by Casassola et al (2015) and Dobon et al (2016), respectively. Pathogenesis related transcripts with Barwin, CAPS and Bet_v_1 domain were identified only in the resistant genotype WL711+ Lr57 indicating a direct link to Lr57 .…”
Section: Discussionmentioning
confidence: 86%
“…The molecular analyses of host pathogen interactions have been restricted to limited number of genes (Casassola et al, 2015; Wang et al, 2015) but with the advances in sequencing technologies it has become affordable to study the complete transcriptomes of the host as well as pathogen. A number of studies have used ESTs (Manickavelu et al, 2010; Dmochowska-Boguta et al, 2015), microarrays (Fofana et al, 2007), serial analysis of gene expression (Chandra et al, 2016), and RNAseq (Zhang et al, 2014; Dobon et al, 2016) to understand the host pathogen relationship between known host genes and specific pathotypes under compatible as well as incompatible interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Ten MIPs including six plasma membrane intrinsic proteins (PIPs) and four tonoplast intrinsic proteins (TIPs) were mainly repressed during days 4 and 8, but increased their transcript abundance 18 DPI (Supplementary Figure S5S). It is possible that their regulation is controlled by the pathogen to improve invasion into plant tissues due to greater flow of water through these membrane pores which allows easier haustorial development (Casassola et al, 2015); however, another study showed that these membrane water channels could facilitate the conduction of H 2 O 2 (Dynowski et al, 2008), and support defense signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Na resistência quantitativa ou parcial há uma variação no grau de resistência, indo de plantas altamente resistentes até altamente suscetíveis (13). O gene de resistência Yr36 que confere resistência à ferrugem amarela do trigo codifica uma proteína com um domínio quinase ligado a um domínio lipídico (27).…”
Section: Principais Genes E Seus Mecanismos De Resistência Em Cereaisunclassified